Activation of the mismatch-specific endonuclease EndoMS/NucS by the replication clamp is required for high fidelity DNA replication - Ishino, Sonoko (Nucleic Acids Res, 2018)
The mismatch repair (MMR) system, exemplified by the MutS/MutL proteins, is widespread in Bacteria and Eukarya. However, molecular mechanisms how numerous archaea and bacteria lacking the mutS/mutL genes maintain high replication fidelity and genome stability have remained elusive. EndoMS is a recently discovered hyperthermophilic mismatch-specific endonuclease encoded by nucS in Thermococcales. We deleted the nucS from the actinobacterium Corynebacterium glutamicum and demonstrated a drastic increase of spontaneous transition mutations in the nucS deletion strain. The observed spectra of these mutations were consistent with the enzymatic properties of EndoMS in vitro. The robust mismatch-specific endonuclease activity was detected with the purified C. glutamicum EndoMS protein but only in the presence of the β-clamp (DnaN). Our biochemical and genetic data suggest that the frequently occurring G/T mismatch is efficiently repaired by the bacterial EndoMS-β−clamp complex formed via a carboxy-terminal sequence motif of EndoMS proteins. Our study thus has great implications for understanding how the activity of the novel MMR system is coordinated with the replisome and provides new mechanistic insight into genetic diversity and mutational patterns in industrially and clinically (e.g. Mycobacteria) important archaeal and bacterial phyla previously thought to be devoid of the MMR system.